Is 2 n + 1 + ( − 1 ) n divisible by 3 for every positive integer n ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( n ) = 2 n + 1 + ( − 1 ) n . When n is odd, let n = 2 m − 1 , where m is a positive integer. Then f ( n ) = 2 2 m − 1 . Since g cd ( 2 , 3 ) = 1 , we can apply Euler's theorem and
f ( n ) ≡ 2 2 m m o d ϕ ( 3 ) − 1 ≡ 2 2 m m o d 2 − 1 ≡ 0 (mod 3) where ϕ ( ⋅ ) denotes the Euler’s totient function, and since 3 is a prime, ϕ ( 3 ) = 3 − 1 = 2 .
Therefore, f ( n ) is divisible by 3 when n is odd.
When n is even, let n = 2 m . Then f ( n ) ≡ 2 2 m + 1 + 1 ≡ 2 ( 2 m + 1 ) m o d 2 + 1 ≡ 2 + 1 ≡ 0 (mod 3) . Again f ( n ) is divisible by 3 when n is even.
Yes , f ( n ) 2 n + 1 + ( − 1 ) n is divisible by 3 for every positive integer n .
Reference: Euler's totient function
Problem Loading...
Note Loading...
Set Loading...
If n is even then 2 n + 1 + ( − 1 ) n ≡ 2 + 1 ≡ 0 m o d 3 . If n is odd then 2 n + 1 + ( − 1 ) n ≡ 1 + 2 ≡ 0 m o d 3 .